Identification and Fine‐Mapping of a Soybean Quantitative Trait Locus on Chromosome 5 Conferring Tolerance to Iron Deficiency Chlorosis. Issue 3 (1st November 2019) - Merry, Ryan; Butenhoff, Karl; Campbell, Benjamin W.; Michno, Jean‐Michel; Wang, Dechun; Orf, James H.; Lorenz, Aaron J.; Stupar, Robert M.
Abstract : Core Ideas: 'Fiskeby III' harbors a combination of abiotic stress traits, including iron deficiency chlorosis (IDC) tolerance. An IDC quantitative trait locus on chromosome Gm 05 was identified in genome‐wide association studies and biparental populations. Fine‐mapping resolved a 137‐kb interval containing strong candidate genes. Iron deficiency chlorosis (IDC) is an important nutrient stress for soybean [ Glycine max (L.) Merr.] grown in high‐pH soils. Despite numerous agronomic attempts to alleviate IDC, genetic tolerance remains the most effective preventative measure against symptoms. In this study, two association mapping populations and a biparental mapping population were used for genetic mapping of IDC tolerance. Quantitative trait loci (QTLs) were identified on chromosomes Gm 03, Gm 05, and Gm 06. Heterogenous inbred families were developed to fine‐map the Gm 05 QTL, which was uniquely supported in all three mapping populations. Fine‐mapping resulted in a QTL with an interval size of 137 kb on the end of the short arm of Gm 05, which produced up to a 1.5‐point reduction in IDC severity on a 1 to 9 scale in near isogenic lines.